Mekanisme Pembuatan Briket Berbasis Limbah Pertanian yang Ramah Lingkungan - Febi Navila Ella Firdani; Sudarti Sudarti (JTPG (Jurnal Teknologi Pertanian Gorontalo), 2022)
The problems that are often encountered are the problem of garbage or waste from human activities, these activities include households, agriculture, factories, and others. The purpose of this research is to reduce waste or waste that is really needed at this time whether it is used for other alternative sources that are environmentally friendly, so that waste or waste from agricultural activities does not continue to increase, organic fertilizer and briquettes or charcoal can be used. In this study using the method of literature review from various international journals. The journal used starts from the past 10 years, namely 2012-2022 and searches for it via Google Scolar. Keywords used when searching journals on Google Scolar such as "agricultural waste processing", "briquette management", and "agricultural waste". Garbage is the remains of human activities that are not reused but can produce a useful new product. There are various types of waste or waste, one of which is agricultural waste which can produce products that are beneficial to the environment or environmentally friendly. Agricultural waste is the part of agricultural plants from the top or shoots to the remaining stems after harvesting activities. Utilization of agricultural waste is very useful for humans, the environment, and other living things. One of the uses of this agricultural waste is as briquettes which are a new alternative source that is environmentally friendly because it comes from various plant residues produced during harvesting activities. Most of the agricultural waste comes from rice. So, the existence of agricultural waste can be used as a new alternative source that is environmentally friendly and inexpensive.